A software costing tool. (c1996) - Akkari, Nesrine N. (1996)
One of the most important problems faced by software developers and users is the prediction of the size of a programming system and its development effort. The aim of the tool presented in this report is to provide the user with an efficient way to calculate or estimate the size and development effort of a programming system. The proposed tool is based on the COCOMO and the Function Point Analysis models. It covers user programming systems written using any of the following programming languages: C, C++, Cobol, Fox/Foxpro, Lisp, Pascal, and Visual Basic.